Knowledge Management Practices in Steel Industries of India: A Comparative Analysis of Public and Private Steel Industries - et. al., Srinibash Dash, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to study the knowledge management practices of steel industries in India. The Indian economy is considered a mixed economy. Indian steel industry having the participation from both private and public sector enterprises is one of the fastest-growing industries in terms of steel production and is also increasingly looking towards export as driving the growth of the industry. Under this study both public and private steel industries are taken into consideration. The study was based on secondary data. This research brings a research report on the impact of Knowledge Management Practices (KMP) in the Indian steel industries. The analysis was made by taking the previous year's data regarding various matters relating to KMP and its pros and cons in the performance of the Indian steel industries. The comparison was done between these two i.e., both public and private steel companies of the country